A profile of obesity in Ireland, 2002 - 2007 - David Madden (University College Dublin, UCD School of Economics, 2010)
Using the nationally representative Slan dataset we take a number of approaches to profile the change in obesity in Ireland over the 2002-2007 period. There is no evidence of either first or second order stochastic dominance between the two years. There is evidence that obesity and overweight are relatively more concentrated amongst males, the old and those with lower educational achievement. While obesity rose slightly over the period this was due to a rise in the average level of body mass index rather than a change in the shape of the distribution. Finally a semi-parametric decomposition of the change in the distribution over time indicates that the change in obesity arose not because of changes in population characteristics but rather the in the impact of these characteristics on body mass index.
hdl:10197/2636
Keywords: I12; I31; I32; 330; Obesity; Body Mass Index; Decomposition